2005
DOI: 10.1111/j.1651-2227.2005.tb01836.x
|View full text |Cite
|
Sign up to set email alerts
|

Developmental delay at 12 months in children born extremely preterm

Abstract: Aim: To evaluate the feasibility and validity of a structured telephone interview to assess the development of children born extremely preterm. Methods: The parents of 88 children born with a gestational age below 28 wk admitted to the neonatal intensive care unit (NICU) at Rigshospitalet, Copenhagen, were interviewed by telephone when their child was 1 y of age, corrected for preterm birth. A fully structured questionnaire on psychomotor function was used (Revised Prescreening Developmental Questionnaire (R‐P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
0
11
0
1
Order By: Relevance
“…Four age‐related forms are available. Parents found the Revised Pre‐screening Developmental Questionnaire (R‐PDQ) interesting and easy to complete, whilst healthcare professionals found it economical and easy to interpret (3). In the case of abnormal results, it is recommended that a re‐evaluation be performed 1 month later.…”
mentioning
confidence: 99%
“…Four age‐related forms are available. Parents found the Revised Pre‐screening Developmental Questionnaire (R‐PDQ) interesting and easy to complete, whilst healthcare professionals found it economical and easy to interpret (3). In the case of abnormal results, it is recommended that a re‐evaluation be performed 1 month later.…”
mentioning
confidence: 99%
“…Norway had five norming and/or validation studies that used the older ASQ‐2 . One Danish translation ASQ:SE‐2 psychometric study and two Danish ASQ‐2 psychometric studies were identified. One Swedish ASQ:SE validation study was identified.…”
Section: Resultsmentioning
confidence: 99%
“…Results for Scandinavian children with concerning screens from the ASQ/ASQ:SE were quite inconsistent compared with US studies where, at a minimum, children were routinely referred to Individuals with Disabilities Education Act EI/ECSE programmes (which are available in every county of every state). These Scandinavian children often had no clearly described follow‐up plan, or they received further assessment (typically with a psychologist or medical subspecialist) based on individualized research protocols . The literature also collectively indicates different follow‐up procedures in different regional municipalities throughout Denmark, Norway, and Sweden .…”
Section: Resultsmentioning
confidence: 99%
“…The answers “no” or “do not know” gave zero points. The questionnaire was filled in during a telephone interview by NICU staff: AL, or nurses trained by attending an interview with AL [3].…”
Section: Clinical Characteristicsmentioning
confidence: 99%
“…The mean score was 14.9 ± 3.9. Regression analysis showed that the scores increased by 1.21±0.28 per month ( p < 0.001) [3]. The age‐adjusted R‐PDQ score had a significant negative skew due to three preterm children scoring below — 2 standard deviations.…”
Section: Clinical Characteristicsmentioning
confidence: 99%